2012
DOI: 10.1111/ans.12013
|View full text |Cite
|
Sign up to set email alerts
|

Improving operating theatre efficiency: an intervention to significantly reduce changeover time

Abstract: Background: Operating theatre inefficiency and changeover delays are not only a significant source of wasted resources, but also a familiar source of frustration to patients and health-care providers. This study aimed to prove that the surgical registrar through active involvement in patient changeover can significantly improve operating room efficiency and minimize delays. Methods: A two-phase prospective cohort study was undertaken, conducted over the course of 4 weeks at a single institution. The only inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 11 publications
1
25
1
Order By: Relevance
“…‘Delay in definitive treatment’ was identified as the most severe clinical management issue from this study and from the national report data 13. In orthopaedic clinical studies on hip fracture patients, delay in definitive treatment was shown to be attributable to patient factors such as age and comorbidities, as well as waiting times to theatre 14 15. In the aggregate results, ‘communication issues or poor documentation’ was in the top seven clinical management issues.…”
Section: Discussionmentioning
confidence: 99%
“…‘Delay in definitive treatment’ was identified as the most severe clinical management issue from this study and from the national report data 13. In orthopaedic clinical studies on hip fracture patients, delay in definitive treatment was shown to be attributable to patient factors such as age and comorbidities, as well as waiting times to theatre 14 15. In the aggregate results, ‘communication issues or poor documentation’ was in the top seven clinical management issues.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Escalating healthcare costs and limited state health budgets necessitate an efficient theatre service to maximise service delivery and reduce costs. [2] The Lancet Commission has highlighted the need for scaling up surgical services in low-and middle-income countries to increase access to essential surgery. [3] Scale-up will place an increased burden on existing resources, further emphasising the importance of optimising use of available theatre time.…”
Section: Researchmentioning
confidence: 99%
“…Surgical care is encompassed in the perioperative period which includes three phases: preoperative, intraoperative, and postoperative. The intraoperative period contains the execution of the surgery; it is of interest as it utilises the operating theatres (OT), and a large proportion of a hospital's total expenses come from here (6).…”
Section: Introductionmentioning
confidence: 99%
“…The OT is a complex environment to optimise, with efficiency influenced by factors such as: case scheduling, cancelled cases, on-time starts, procedure time variation (which is influenced by equipment, patient factors, individual surgeon skill, and case complexity), turnover time, administrative factors (i.e., bed management), and the surgical team (i.e., junior staff who are still training) (6,8,9). Understanding what factors contribute to efficiency in the intraoperative period can allow for improvements to be formulated and implemented; process mapping could help to achieve this.…”
Section: Introductionmentioning
confidence: 99%